Safety and Efficacy Profile of Echinacea purpurea to Prevent Common Cold Episodes: A Randomized, Double-Blind, Placebo-Controlled Trial. (16th September 2012) - Jawad, M.; Schoop, R.; Suter, A.; Klein, P.; Eccles, R.
Abstract : Objective . To investigate the safety (risk) and efficacy (benefit) of Echinacea purpurea extract in the prevention of common cold episodes in a large population over a 4-month period. Methods . 755 healthy subjects were allocated to receive either an alcohol extract from freshly harvested E. purpurea (95% herba and 5% root) or placebo. Participants were required to record adverse events and to rate cold-related issues in a diary throughout the investigation period. Nasal secretions were sampled at acute colds and screened for viruses. Results . A total of 293 adverse events occurred with Echinacea and 306 with placebo treatment. Nine and 10% of participants experienced adverse events, which were at least possibly related to the study drug (adverse drug reactions). Thus, the safety of Echinacea was noninferior to placebo. Echinacea reduced the total number of cold episodes, cumulated episode days within the group, and pain-killer medicated episodes. Echinacea inhibited virally confirmed colds and especially prevented enveloped virus infections (P < 0.05 ). Echinacea showed maximal effects on recurrent infections, and preventive effects increased with therapy compliance and adherence to the protocol. Conclusions . Compliant prophylactic intake of E. purpurea over a 4-month period appeared to provide a positive risk to benefit ratio.